Pharmacologically induced reversible hypometabolic state mitigates radiation induced lethality in mice. Issue 1 (December 2017) - Ghosh, Subhajit; Indracanti, Namita; Joshi, Jayadev; Ray, Jharna; Indraganti, Prem
Abstract Therapeutic hypothermia has proven benefits in critical care of a number of diseased states, where inflammation and oxidative stress are the key players. Here, we report that adenosine monophosphate (AMP) triggered hypometabolic state (HMS), 1–3 hours after lethal total body irradiation (TBI) for a duration of 6 hours, rescue mice from radiation-induced lethality and this effect is mediated by the persistent hypothermia. Studies with caffeine and6 N-cyclohexyladenosine, a non-selective antagonist and a selective agonist of adenosine A1 receptor (A1AR) respectively, indicated the involvement of adenosine receptor (AR) signaling. Intracerebroventricular injection of AMP also suggested possible involvement of central activation of AR signaling. AMP, induced HMS in a strain and age independent fashion and did not affect the behavioural and reproductive capacities. AMP induced HMS, mitigated radiation-induced oxidative DNA damage and loss of HSPCs. The increase in IL-6 and IL-10 levels and a shift towards anti-inflammatory milieu during the first 3–4 hours seems to be responsible for the augmented survival of HSPCs. The syngeneic bone marrow transplantation (BMT) studies further supported the role of radiation-induced inflammation in loss of bone marrow cellularity after TBI. We also showed that the clinically plausible mild hypothermia effectively mitigates TBI induced lethality in mice.